The integration of major fuel source markets in China: Evidence from panel cointegration tests - Ma, H.; Oxley, Leslie (Elsevier, 2010)
The paper tests for energy price co-movement in China over the 'new regime' as part of a strategy to test for the existence of a national energy market. Panel cointegration test statistics suggest that not all energy commodities are spatially homogenous in prices and the processes of energy price cointegration are different over time and over groups of fuels. The statistics demonstrate China's gradual, spatially partial and idiosyncratic energy reform process. Coal and electricity price series have co-moved since 2003, while the national panel cointegration test statistics suggest that gasoline and diesel price series have co-moved since 1997. Regional panel tests also show that there are apparently differences in the emergence of energy price co-movement. This suggests that regional energy markets have emerged in China. One of the important lessons of the research is that an energy market has, to some extent, already emerged in China and, as a consequence, energy prices are much less distorted than previously. If correct, this fact is of major global significance both in terms of future environmental effects and future trade and investment negotiations as China is seen internationally as a 'market driven economy'. © 2010 Elsevier B.V.